The second Herschel–ATLAS Data Release – III. Optical and near-infrared counterparts in the North Galactic Plane field. Issue 1 (18th January 2018) - Furlanetto, C; Dye, S; Bourne, N; Maddox, S; Dunne, L; Eales, S; Valiante, E; Smith, M W; Smith, D J B; Ivison, R J; Ibar, E
Abstract: This paper forms part of the second major public data release of the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS). In this work, we describe the identification of optical and near-infrared counterparts to the submillimetre detected sources in the 177 deg 2 North Galactic Plane (NGP) field. We used the likelihood ratio method to identify counterparts in the Sloan Digital Sky Survey and in the United Kingdom InfraRed Telescope Imaging Deep Sky Survey within a search radius of 10 arcsec of the H-ATLAS sources with a 4σ detection at 250 μm. We obtained reliable ( R ≥ 0.8) optical counterparts with r  < 22.4 for 42 429 H-ATLAS sources (37.8 per cent), with an estimated completeness of 71.7 per cent and a false identification rate of 4.7 per cent. We also identified counterparts in the near-infrared using deeper K -band data which covers a smaller ∼25 deg 2 . We found reliable near-infrared counterparts to 61.8 per cent of the 250-μm-selected sources within that area. We assessed the performance of the likelihood ratio method to identify optical and near-infrared counterparts taking into account the depth and area of both input catalogues. Using catalogues with the same surface density of objects in the overlapping ∼25 deg 2 area, we obtained that the reliable fraction in the near-infrared (54.8 per cent) is significantly higher than in the optical (36.4 per cent). Finally, using deep radio data which covers a small region of the NGP field, we found that 80–90 per cent of our reliable identifications are correct.